Integrating Islamic Values into School-Based Character Education - Awaliyah Fitri, Sofia Ratna; Arifin, Bambang Samsul; Hasanah, Aan (Bestari, 2024)
This study seeks to elucidate the incorporation of Islamic ideals into character education. The amalgamation of character education with Islamic principles encompasses components such as the comprehension of Islamic ethics, emotional engagement with morals, and acts of devotion. Islam, as a value-laden faith, serves as a significant foundation for character education references. This study examines the concepts inherent in Islamic teachings that pertain to character and their implementation. This study employs the analytical descriptive technique, a research approach aimed at elucidating theories as articulated by experts in character education grounded in Islamic values. The study’s results indicate that Islamic education and character education aim to cultivate pupils with noble and resilient principles. Islamic education, with its explicit and comprehensive framework, adheres strictly to the teachings of the Qur’an and Al-Sunnah.